They say we are infidels : on the run from ISIS with persecuted Christians in the Middle East - Belz, Mindy (Tyndale Momentum, an imprint of Tyndale House Publishers, Inc., 2016)
"Examines the escalating persecution of Christian groups in the Middle East by ISIS forces, offering testimony of the brutalization and annihilation of Christians along with their refusal to abandon their faith in the face of it all,"--NoveList.